Analisis Ukuran Batubara Menggunakan Metode Statistical Quality Control di PT. Mifa Bersaudara - Gaustama Putra; Rofi Rosalinda (Jurnal Optimalisasi, 2020)
PT. Mifa Brothers are located in Peunaga Cut Ujong Village, Meureubo, West Aceh, Aceh Province, which is engaged in coal mining, which has 2 types of size, namely small size (fines coal 50 mm) and large size (lumpy coal 200 mm). The problem that occurs in this company is that coal size is often not under buyer demand, 2 types of coal size are often mixed, the coal size sampling process is still done manually and takes a long time. Therefore it is necessary to do quality control to determine the coal size control limits so that the company can directly monitor from the company control chart, to facilitate the company in improving processes that go beyond the statistical control limits. Quality control can be carried out by using statistical tools to control the proportion of errors (p-chart) of daily/individual data from coal size sampling results. In January 2019, 10 ships and 70 barges totaling 550.000 mt, so the sample units produced were 6860,1 increases (20580.2 kg), coal size mismatch data were 12592 kg, from the map control calculation of the proportion of errors obtained for P 6,11853, CL 6,1185, UCL 6,440771 and LCL 5,796223. From the results of data processing, calculation of the control map from the proportion of errors turns out that the 5th and 9th observations are outside the limits of statistical control, it is necessary to revise the final results and obtained for P 4,782038, CL 4, 782024, UCL 5,041432, LCL 4,522616.